Exploring an e-learning community's response to the language and terminology use in autism from two massive open online courses on autism education and technology use - Lei, J; Jones, L; Brosnan, M (SAGE Publications, 2021)
Prior research has identified the divergence across different stakeholder groups in the semantic choice of language when describing autism, as members of the autism and autistic community preferred to use identity-first language (autistic person), whereas professionals were more likely to use person-first language (person with autism). This study explored 803 e-learners’ responses from their comments across two massive open online courses on autism education held between 2017 and 2019. Comments from members of the autistic and autism community and professionals were analysed together using thematic analysis, to identify shared opinions on what, why and how language should be used when describing autism across stakeholder groups. Learners agreed that autistic individuals should guide others on which terminology to use when describing autism and that the diagnostic label is a way to facilitate understanding across stakeholder groups and help the individual gain access to support. Semantic language choices may matter less as long as the person’s difficulties are clearly acknowledged, with adaptations made to meet their specific needs. Adding to a growing body of literature on terminology use in autism research and practice, we highlight that consideration for semantic choice of language use should focus on communicating an individual’s strengths and differences.